Light as a Cure in COVID-19: A Challenge for Medicine - Laura Marinela Ailioaie; Constantin Ailioaie; Gerhard Litscher (Photonics, 2022)
Light and lasers, as high-tech devices whose medical potential has yet to be fully discovered, have made important contributions to medicine, even in the current pandemic. The main aim of this review was to investigate how light was applied as a therapeutic tool during a crisis triggered by COVID-19. Another goal was to encourage scientists and industry to quickly design new at-home photobiomodulation therapy (PBMT) and/or antimicrobial photodynamic therapy (aPDT) easy to use systems to end this pandemic, especially for those who believe in high-tech but would never get vaccinated. This review revealed that PBMT has been successfully applied as adjunct therapy, in combination with conventional medical treatment, and as a pioneering action in SARS-CoV-2 infection, demonstrating significant improvements in airway inflammation and general clinical condition of patients, a faster recovery, avoiding intensive care unit (ICU) hospitalization, mechanical ventilation, mortality, and overcoming long-term sequelae. Application in only a limited number of cases strongly suggests the need for future randomized, placebo-controlled clinical trials to objectively determine the action and effects of PBMT in COVID-19. Implementation of unparalleled theragnostics methods and light-based techniques for disinfection of spaces, air, skin, mucosae, and textures to decrease the load of SARS-CoV-2 virus would save lives, time, and money. In this ongoing and challenging search for the seemingly intangible end of this pandemic, a non-invasive, easily accessible, safe, and side-effect-free adjuvant method appears to be PBMT, alone or in synergistic combination with aPDT, which has been shown to work in COVID-19 and opens unprecedented potential for use as home self-treatment to end the pandemic.